PENERAPAN MEDIA GAMBAR DALAM PEMBELAJARAN PAI PADA ANAK USIA DINI - Neng Awalia Farida; Ridwan Agustian Nur (Institut Madani Nusantara, 2022)
This study has the potential to enrich educational information, especially in the field of educational technology, and determine visual media and their strategic value for teachers, parents, students, and education practitioners in the school itself. . This type of survey is a qualitative field survey using a descriptive survey method. The data collection method was obtained by using: 1). Observation, 2). Job interview, 3). documentation. Although the data analysis method used is descriptive qualitative. The results showed that the visual media used in PAI learning at RA Nurul Mu'minin Bojonggenteng were still images in the form of posters, caricatures, and cartoons. Video media that are films and VCD images are combined with television. Visual media RANurul Mu'minin Bojonggenteng is used to make teaching methods more communicative and effective. The application of visual media in PAI PAI learning at RA Nurul Mu'minin Bojonggenteng has been successfully implemented.